A Seroprevalence Survey of Maedi-Visna Among Twenty-Four Ovine Floks from Twelve Regions of China - Ke-shan ZHANG; Ji-jun HE; Yong-jie LIU; You-jun SHANG; Xiang-tao LIU (Journal of Integrative Agriculture, 2013)
Maedi-visna virus (MVV) is an ovine lentivirus that is widespread in many countries worldwide. Both clinical and subclinical MVV infections cause substantial economic losses. MVV infection in live sheep is usually diagnosed serologically, with antibody-positive sheep being regarded as infected. There have been few reports of maedi-visna in China, with no detailed epidemic analysis of MVV infection in ovine herds. In order to investigate the seroprevalence and spatial distribution of maedi-visna among ovine flocks in China, a total of 672 serum samples were collected from different ovine flocks in 12 regions (provinces, autonomous regions or municipalities) of China in 2011, and serum antibody levels were determined using a commercial ELISA Kit. This study represents the first investigation of the seroepidemiology of maedi-visna in China, indicating a circulation of MMV among sheep.